2012
DOI: 10.5863/1551-6776-17.2.173
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Oseltamivir and Oseltamivir Carboxylate in a Critically Ill Pediatric Patient Receiving Extracorporeal Membrane Oxygenation and Continuous Venovenous Hemodialysis

Abstract: This report details the pharmacokinetics of oseltamivir and oseltamivir carboxylate following administration of high-dose oseltamivir in a critically ill child receiving extracorporeal membrane oxygenation (ECMO) and continuous venovenous hemodialysis (CVVHD). A 6-year-old critically ill male patient suffering from a presumed viral illness was transferred to our institution's pediatric intensive care unit from an outside hospital after developing respiratory failure and cardiomegaly. ECMO and oseltamivir thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…This drug was recommended for severe influenza A (H1N1) infection during the 2009 novel influenza H1N1 pandemic . Previous studies of children have indicated that changes in oseltamivir PK during ECMO were not significant . In a prospective case study of 3 children (6‐15 years old), the oseltamivir dosage was doubled and CVVH was performed following the ECMO protocol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This drug was recommended for severe influenza A (H1N1) infection during the 2009 novel influenza H1N1 pandemic . Previous studies of children have indicated that changes in oseltamivir PK during ECMO were not significant . In a prospective case study of 3 children (6‐15 years old), the oseltamivir dosage was doubled and CVVH was performed following the ECMO protocol.…”
Section: Resultsmentioning
confidence: 99%
“…However, owing to the limited sample size, a dosing recommendation could not be made . An analysis of the other 6‐year‐old child revealed that the differences in oseltamivir and oseltamivir carboxylate concentrations between the pre‐oxygenator and post‐oxygenator of ECMO were small, suggesting little drug removal by the oxygenator during ECMO …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that oseltamivir administered orally or via oro/naso-gastric tube is well absorbed in critically ill patients and reaches plasma levels comparable to those in ambulatory patients [80]. Similarly, several observational studies indicate that enteric oseltamivir reaches comparable plasma concentrations to non-critically ill patients in those receiving extracorporeal membrane oxygenation (ECMO) and renal replacement therapy [80][81][82][83][84][85][86][87], although dosing should be reduced in patients with significant renal impairment. There is scant evidence that increased NAI dosing (e.g., twice daily dosing) in critically ill patients provides additional clinical benefit than standard dosing [80,[88][89][90][91][92].…”
Section: Treatment Of Influenzamentioning
confidence: 99%